0861 The Relationship between Continuous Positive Airway PressureTreatment in Obstructive Sleep Apnea SyndromePatients and Sensorineural Hearing Loss: A Prospective Cohort Study. (12th April 2019) - Chi, Jessie Chao-Yun; Hua, Ting; Liu, Stanley Yung
Abstract: Introduction: Obstructive sleep apnea syndrome (OSAS) may be related to tinnitus and hearing loss. However, there are no prospective cohort studies to discuss the relationship between sensorineural hearing loss (SNHL) and continuous positive airway pressure (CPAP) treatment in OSAS patients. Our study is to analyze the correlation between these. Methods: 100 participants who had SNHL and clinical symptoms of OSAS from Sep 1 st 2016 to Jun 1 st 2018 were included and followed at least 1 year. AHI <5 (N=19) and surgery treatment (N=4) were excluded. The 77 participants were categorized into 2 groups: OSAS with CPAP treatment (N=28) and OSAS without treatment (N=49). Pure tone audiometry (PTA) with different frequencies (low, medium, high, and average tone) for a period of time (3, 6, 9, and 12 months) was recorded. The risk factors, such as onset of hearing loss, severity of OSAS, hypertension, diabetics, stroke, depression, smoking, and alcohol drinking, were also included. Valid samples were analyzed in generalized estimating equation by SPSS for windows 17.0. Results: Analysis included 77 participants. Unilateral SNHL can be alleviated by CPAP therapy for 6 months (Average tone: p= 0.021; Low tone: p=0.003; Medium tone: p=0.012; High tone: p=0.607); 9 months (Average: p= 0.035; Low: p=0.002; Medium: p=0.005; High: p=0.804); 12 months (Average: p= 0.03; Low: p=0.000; Medium: p=0.000; High: p=0.558). There was no benefit to CPAP therapy in 3 months (p>0.05). Age, male, smoking, alcoholic drinking, coronary artery diseases, hypertension, and apnea-hypoxia index are related to SNHL (p<0.05). Conclusion: CPAP treatment for at least 6 months in OSAS patients can improve unilateral hearing ability (average, low, and medium tone). There is no any benefit to CPAP therapy in high tone SNHL. CPAP short-term treatment (3 months) cannot benefit SNHL, either. Support (If Any): Taichung Hospital, Ministry of Health and Welfare Study Program